EFFECT OF CAPITAL STRUCTURE, SIZE OF COMPANY, WORKING CAPITAL TO THE PERFORMANCE OF THE COMPANY AND ITS IMPACT ON THE VALUE OF THE COMPANY - Estuti Fitri Hartini; Susanti Widhiastuti (Sekolah Tinggi Ilmu Ekonimi IPWI Jakarta, 2018)
The capital structure is very important to finance the company so that its management can run well and have an impact on the increase of income and capital structure that optimizes the balance between risk and return rate maximizing the stock price of the company. Corporate value can also be influenced by the company's performance profitability, which in this study proxied by sales growth and working capital proxied by the amount of inventory. The growth of sales will determine the extent to on how the company can maintain its profitability in accordance with the company's expectations and the amount of inventory as a current asset to maintain the liquidity of the company that impacts on rising corporate value. Weston and Coveland (1992) define profitability as the extent to on how the firms generate profits from sales and corporate investments.The purpose of this research is to analyze the influence of capital structure on company performance; to analyze the effect of firm size on company performance; to analyze the effect of Working Capital on Corporate Performance; to analyze the effect of Capital Structure directly on Corporate Value; to analyze the effect of Company Size directly on Corporate Value; to analyze the effect of Working Capital directly on Corporate Value; to analyze the effect of the Company's Performance on Corporate Value.This research is based on the type of quantitative research, and path analysis method used to test the effect of exogenous variables on endogen, using SPSS version 16 software.Result of research, Capital structure has no significant effect on company performance; Company size has a significant effect on company performance; Working capital has significant effect on company performance; Capital Structure has no significant effect on company value; The size of the firm has no significant effect on firm value; Working capital has a significant positive effect on company value; Company performance has no significant effect on company value.Â Keywords: Capital Structure, Company Size, Working Capital, Corporate Performance, Corporate Value.